Low serum transferrin correlates with acute‐on‐chronic organ failure and indicates short‐term mortality in decompensated cirrhosis. (17th August 2016) - Bruns, Tony; Nuraldeen, Renwar; Mai, Martina; Stengel, Sven; Zimmermann, Henning W.; Yagmur, Eray; Trautwein, Christian; Stallmach, Andreas; Strnad, Pavel
Abstract: Background & Aims: Iron represents an essential, but potentially harmful micronutrient, whose regulation has been associated with poor outcome in liver disease. Its homeostasis is tightly linked to oxidative stress, bacterial infections and systemic inflammation. To study the prognostic short‐term significance of iron parameters in a cohort study of patients with decompensation of cirrhosis at risk of acute‐on‐chronic liver failure (ACLF). Methods: Ferritin, transferrin, iron, transferrin saturation (TSAT) and hepcidin were determined in sera from 292 German patients hospitalized for decompensation of cirrhosis with ascites, of which 78 (27%) had ACLF. Short‐term mortality was prospectively assessed 30 and 90 days after inclusion. Results: Transferrin concentrations were significantly lower, whereas ferritin and TSAT were higher in patients with ACLF compared to patients without ACLF ( P ≤.006). Transferrin, TSAT and ferritin differentially correlated with the severity of organ failure, active alcoholism and surrogates of systemic inflammation and macrophage activation. As compared with survivors, 30‐day non‐survivors displayed lower serum transferrin ( P= .0003) and higher TSAT ( P= .003), whereas 90‐day non‐survivors presented with higher ferritin ( P= .03) and lower transferrin ( P= .02). Lower transferrin (continuous or dichotomized at 87 mg/dL) and consecutively higher TSAT (continuous or dichotomized >41%) indicated increased mortality within 30 days and remained significant after adjustment for organ failure and inflammation in multivariate regression models and across subgroups of patients. Conclusion: Among the investigated indicators of iron metabolism, serum transferrin concentration was the best indicator of organ failure and an independent predictor of short‐term mortality at 30 days.